2001
DOI: 10.1046/j.1440-1711.2001.00969.x
|View full text |Cite
|
Sign up to set email alerts
|

Elevation of intracellular calcium levels contributes to the inhibition of nitric oxide production by atrial natriuretic peptide

Abstract: Atrial natriuretic peptide (ANP) attenuates LPS‐induced inducible nitric oxide synthase (iNOS) expression in murine macrophages by destabilizing iNOS mRNA. Because elevated intracellular free Ca2+ levels [Ca2+]i reduce iNOS mRNA stability, the aim of the present study was to determine whether inhibition of iNOS by ANP is due to alterations in intracellular calcium. As determined by fluorescence photometry, ANP (10–7 and 10–6 mol/L) was shown to elevate intracellular calcium levels in bone marrow‐derived macrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…It was reported that application of TG is also associated with activation of programmed cell death in various liver epithelial cells: human liver-derived cell line, Huh7 cells (Xie et al, 2002;Chae et al, 2004), different hepatoma cell lines (Sohn et al 2003), and primary rodent hepatocytes (Li and Holbrook, 2004;. Moreover, TG can modulate NO production in macrophages as previously reported (Jordan et al, 1995;Jun et al, 1996;Park et al, 1996;Chen BC et al, 2001;Kiemer and Vollmar, 2001;Chen YJ et al, 2005;Kmonickova et al, 2005). TG can stimulate and/or inhibit NO production and iNOS expression mostly depending on an increase in [Ca 2+ ] i , immunological stimulation, and protein kinase C status of macrophages.…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…It was reported that application of TG is also associated with activation of programmed cell death in various liver epithelial cells: human liver-derived cell line, Huh7 cells (Xie et al, 2002;Chae et al, 2004), different hepatoma cell lines (Sohn et al 2003), and primary rodent hepatocytes (Li and Holbrook, 2004;. Moreover, TG can modulate NO production in macrophages as previously reported (Jordan et al, 1995;Jun et al, 1996;Park et al, 1996;Chen BC et al, 2001;Kiemer and Vollmar, 2001;Chen YJ et al, 2005;Kmonickova et al, 2005). TG can stimulate and/or inhibit NO production and iNOS expression mostly depending on an increase in [Ca 2+ ] i , immunological stimulation, and protein kinase C status of macrophages.…”
Section: Introductionmentioning
confidence: 66%
“…We have previously observed (Kmonickova et al, 2005) that TG suppressed immunologically induced high-output NO production that was accompanied by decreased number of viable mouse peritoneal macrophages in culture. Although iNOS is traditionally considered as Ca 2+ independent, it was shown that an increase in [Ca 2+ ] i caused by TG and other ionophores downregulates iNOS mRNA induction and NO synthesis in lipopolysaccharide-stimulated macrophages (Jordan et al, 1995;Kiemer and Vollmar, 2001). The differential effects of TG in the 0-24 h and 24-48 h periods are noteworthy and may be correlated with different degrees of activation of the basal iNOS pathway observed immediately after collagenase method isolation or 24 h after cell isolation.…”
Section: Discussionmentioning
confidence: 99%
“…Thus far, there is only conflicting evidence from a few studies of such a possible relation, some showing upregulation of eNOS and iNOS by ANP and BNP 23,24 and others downregulation of tumor necrosis factor-␣ (TNF-␣) and, indirectly, iNOS by ANP. [25][26][27] Although strictly speaking, the latter studies were performed using ANP, both ANP and BNP appear to have identical functions. 28 Therefore, whereas upregulation of eNOS and iNOS should improve FMD as shown by exogenous administration of BNP, albeit in healthy individuals, 11,12 downregulation of TNF-␣ and consequently iNOS may impair FMD further.…”
Section: Discussionmentioning
confidence: 99%
“…After 20 h, the concentration of nitrite, a stable metabolite of NO, was measured in the supernatants by Griess assay as described previously (58). Briefly, 90 l of 1% sulfanilamide in 5% H 3 PO 4 and 90 l of 0.1% N-(1-naphthyl)ethylenediamine dihydrochloride in H 2 O were added to 100 l of the cell culture supernatant followed by absorbance measurement at 550 nm and the reference wavelength 630 nm using a Tecan Sunrise microplate reader.…”
Section: Methodsmentioning
confidence: 99%